Analysis of Sharia Principles Implementation in Istishna' Contracts and Its Impact on Customer Satisfaction: A Qualitative Descriptive Study at PT. Mari Beri Faedah - Aan Fajar Wijaya; Sri Hartono; Arif Hartono (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2025)
This study analyzes the implementation of sharia principles in the istishna' contract and its impact on customer satisfaction at PT. Let's Give Benefits (MARIFA). This study aims to map the integration of the principles of Rabbaniyyah, Akhlaqiyyah, Waqi'iyyah, and Insaniyyah in the framework of istishna' and uncover their contribution in shaping holistic customer satisfaction. We used a descriptive qualitative approach with ethnographic methods, collecting data through participatory observation and in-depth interviews with 13 informants from directors, employees, and customers. Data analysis to obtain comprehensive findings. The results of the study revealed that MARIFA has succeeded in operationalizing the four sharia principles. The Rabbaniyyah principle gives rise to spiritual satisfaction through usury-free transactions and the creation of "houses of blessings". Akhlaqiyyah builds customer trust through integrity and professional responsibility. Waqi'iyyah allows for realistic adaptation to customer needs and constraints, while Insaniyyah fosters emotional loyalty through inclusive service and a personal touch. However, the study also identified operational friction points, such as internal coordination challenges and variations in principle understanding at the field level, that mediate ideality with practice. Our discussions highlighted that customers' perceived sharia compliance creates unique value that goes beyond mere functional satisfaction. In conclusion, the integration of sharia principles in the istishna' contract contributes significantly to the realization of holistic customer satisfaction. The implications of this study offer an operational roadmap for the Islamic property industry. Future research is suggested to conduct multi-case studies, quantitative data triangulation, and exploration of value internalization in employees to enrich the findings.